Qualidade de vida dos pacientes internados no centro de tratamento de queimados de um hospital do Estado do RN - Bezerril, Fernanda dos Santos (2016)
The objective of the study was to evaluate the quality of life of hospitalized patients at the Burn Hospital of a Public Hospital. Cross-sectional study with quantitative approach. The present study addressed the quality of life of patients, and their demographic data partners. The instrument chosen was the SF-36 quality of life questionnaire (The Medical Outcomes Study-36-item Short-Form Health Survey). The sample consisted of 14 patients. It was observed that 79% were male. The age group with the highest index was 35 to 39 years, making up 36%. Regarding Quality of Life, the pain and vitality appear with greater commitment, followed by the general state. The domains, "Functional Capacity," "Limitations," "Social," "Emotional," and "Mental Health, appear between" Good "and" Excellent. " It is concluded that it is of fundamental importance that health professionals attend to the knowledge of the aspects that interfere in the quality of life of these patients, qualifying their assistance and improving the treatment.